The effect of infliximab on bone healing in osteoporotic rats - Durmuslar, M. Cenk; Turer, Akif; Balli, UMUT; BALLI, UMUT; Yilmaz, Zehra; Onger, Mehmet Emin; Celik, H. Hamdi; Vatansever, Alper (My University, 2016)
Purpose: The aim of this study was to evaluate the effect of the infliximab on autogenous-mediated bone regeneration and resorption of autogenous graft in the ovariectomised rat model.